Frequency of coprescription and potential risk of bronchospasm in Colombian patients users of topical antiglaucomatous betablockers and bronchodilators - Machado-Alba, Jorge Enrique; Hoyos-Soto, Valentina (Vitae, 2014)
Background: Cardiovascular and respiratory effects of adrenergic agonists used in diseases like chronic obstructive pulmonary disease (COPD), and β-blockers used in glaucoma generate competitive antagonism on the same adrenergic receptor when used simultaneously with the aggravation that the β-blockers can precipitate bronchospasm. Objective: Determine de frequency of coprescription and potential risk of interaction between bronchodilators and topical antiglaucomatous β-blockers for glaucoma in a database of Colombian patients. Methods: Cross-sectional study in patients older than 40 years treated for bronchial disorders and glaucoma between January 1 and October 31, 2012. We used information about 6.2 million population database of individuals enrolled in Health System of Colombia. In the database it was assessed all prescription records of topical β-blockers and any bronchodilators and the frequency of potential risk of developing drug-induced bronchospasm. The identified patients were informed to the physician responsible to the health attention. Results: We found 1756 patients were receiving topical β-blockers and bronchodilators. Most were women (63.2 %), mean age 73.3 ± 11.1 years, in 61 cities. The antiglaucoma drugs more employees were: timolol (67.5 % of patients), timolol/dorzolamide (18.8 % of patients) and bronchodilators: salbutamol (43.8 % of patients) and ipratropium (41.8 % of patients). The more frequent risk associations of bronchospasm were: salbutamol + timolol (n = 890, 50.6 % of patients), ipratropium bromide + timolol (n = 827, 47.1 %) salbutamol + timolol + dorzolamide (n = 258, 14.6 % of patients) and ipratropium bromide + timolol + dorzolamide (n = 255, 14.5 % of patients). Conclusions: The database research of Negative Outcomes Associated with Medication is useful to know problems in prescription of many therapies. There are potential interactions between antiglaucoma drugs and bronchodilators that increase the risk of precipitating bronchospasm in patients who present asthma, COPD and glaucoma in Colombia. Implementing strategies that link drug dispensers and medical insurers can reduce risks associated with the medication.